2007
DOI: 10.1557/jmr.2007.0281
|View full text |Cite
|
Sign up to set email alerts
|

Phase development during mixed-oxide processing of a [Na0.5K0.5NbO3]1−x–[LiTaO3]x powder

Abstract: Powders of the solid lead-free piezoelectric ceramic solution [Na0.5K0.5NbO3]1−x–[LiTaO3]x, x = 0.06, were produced using a mixed-oxide process. Phase analysis indicated the formation of an orthorhombic solid solution at 800 °C, which coexisted with intermediate binary niobate and tantalate phases. A tetragonal main-phase solid solution was formed at ⩾950 °C, along with minor quantities of a tungsten bronze phase. Addition of 3 wt% excess alkali carbonates to the starting powders allowed the orthorhombic solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…However, the values of peak intensity ratio of all the Sb-modified samples were much lower, ∼0.5-0.8. This change suggests that the LiSbO 3 solid solutions are mainly tetragonal with some co-existing orthorhombic phase, thus giving intensity ratios slightly higher than expected for single-phase tetragonal samples 18 . Second-phase LiSbO 3 was detected in the x = 0.1 samples (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…However, the values of peak intensity ratio of all the Sb-modified samples were much lower, ∼0.5-0.8. This change suggests that the LiSbO 3 solid solutions are mainly tetragonal with some co-existing orthorhombic phase, thus giving intensity ratios slightly higher than expected for single-phase tetragonal samples 18 . Second-phase LiSbO 3 was detected in the x = 0.1 samples (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The XRD data (Fig. 1) showed little evidence of peak broadening, but a previous study into phase development during conventional powder calcination of NKN-LT 18 indicated that d-spacings were insensitive to small changes in phase composition, and hence no noticeable XRD peak broadening would be observed.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Fig. 1 shows the XRD patterns of (1 − x) NKLNTx MnO samples which had been sintered at 1025°C for 2 h. The intensity ratio of the pair of peaks at 2θ = 45-46.5°in each pattern was used as an indication of the tetragonal/orthorhombic phase content 22 . The lower angle peak in the pair corresponds to the (220) peak of an orthorhombic NKN-LT phase, or the (002) peak of the tetragonal phase of NKN-LT 23,24 .…”
Section: Introductionmentioning
confidence: 99%